Dexmedetomidine Does Not Affect Evoked Potentials During Spine Surgery. (August 2015) - Rozet, Irene; Metzner, Julia; Brown, Marcia; Treggiari, Miriam M.; Slimp, Jefferson C.; Kinney, Greg; Sharma, Deepak; Lee, Lorri A.; Vavilala, Monica S.
<x xml:space="preserve">Abstract</x> BACKGROUND: The effect of dexmedetomidine on evoked potentials (EPs) has not been elucidated. We aimed to investigate the effect of dexmedetomidine on somatosensory, motor, and visual EPs. METHODS: After IRB approval, 40 adult patients scheduled for elective spine surgery using total IV anesthesia with propofol and remifentanil were randomly assigned to receive either dexmedetomidine (n = 20) or placebo (n = 20) in a double-blind, placebo-controlled trial. After obtaining informed consent, positioning, and baseline EPs recording, patients were randomly assigned to either IV dexmedetomidine 0.6 μg/kg infused over 10 minutes, followed by 0.6 μg/kg/h, or a corresponding volume of IV normal saline (placebo). EP measures at 60 ± 30 minutes after initiation of study drug were defined as T1 and at 150 ± 30 minutes were defined as T2. Changes from baseline to T1 (primary end point) and from baseline to T2 (secondary end point) in EP latencies (milliseconds) and amplitudes (microvolts) were compared between groups. Data presented as mean ± SD (95% confidence interval). RESULTS: Data from 40 patients (dexmedetomidine: n = 20; age, 54 ± 3 years; 10 males; placebo: n = 20; age, 52 ± 2 years; 5 males) were analyzed. There was no difference between dexmedetomidine versus placebo groups in primary end points: change of somatosensory EPs at T1, latency: 0.01 ± 1.3 (−0.64, 0.65) vs 0.01 ± 1.3 (−0.64, 0.65), P = 0.43 (−1.24, 0.45); amplitude: 0.03 ± 0.14 (−0.06, 0.02) vs −0.01 ± 0.13 (−0.07, 0.05), P = 0.76 (−0.074, 0.1); motor EPs amplitude at T1: 65.1 ± 194.8 (−35, 165; n = 18) vs 109.2 ± 241.4 (−24, 243; n = 16), P = 0.57 (−113.5, 241.57); visual EPs at T1 (right eye), amplitude: 2.3 ± 3.6 (−0.4, 5.1; n = 11) vs 0.3 ± 6.0 (−3.3, 3.9; n = 16), P = 0.38 (−6.7, 2.6); latency N1: 2.3 ± 3.6 (−0.4, 5.1) vs 0.3 ± 6.0 (−3.3, 3.9), P = 0.38 (−6.7, 2.6); latency P1: −1.6 ± 13.4 (−11.9, 8.7) vs −1.4 ± 8.1 (−6.3, 3.5), P = 0.97 (−9.3, 9.7) or secondary end points. There were no differences between right and left visual EPs either at T1 or at T2. CONCLUSIONS: In clinically relevant doses, dexmedetomidine as an adjunct to total IV anesthesia does not seem to alter EPs and therefore can be safely used during surgeries requiring monitoring of EPs.